Role of oxygen absorbers in food as packaging material, their characterization and applications - Prerna Gupta
To preserve the environment and to prevent the damage caused by packaging materials, the development of biodegradable, organic, and nano-active films for packaging is progressively being accentuated. As the demand for getting fresh and preservative-free food is increasing, an improved level of clarity and stability for consumers about the packaging is required. Presently, oxygen scavengers are used in the form of films, sachets, powders, or as part of the packaging material itself along with other means of preservation such as the use of chemicals, reduced water activity, pH, multilayer composite material, and or vacuum or modified packaging. Today$1 (Bs current demand increases their incorporation directly into the packaging material rather than being a part of the food itself. The present review, therefore, is based on the availability of types of natural sources of oxygen scavenging systems like antioxidants, and nano iron, and their possible scope of use in the food packaging industry.s